Anxiety, Depression and Post-Traumatic Stress Disorder after Earthquake - Thapa, Prakash; Acharya, Lumeshor; Bhatta, Bhup Dev; Paneru, Suman Bhatta; Khattri, Jai Bahadur; Chakraborty, Prashant Kumar; Sharma, Rajasee (Journal of Nepal Health Research Council, 2018)
Background: Prevalence of anxiety, depression and post traumatic stress disorder is high after earthquake. The aim of the study is to study the prevalence and comorbidity of commonly occurring psychological symptoms in people exposed to Nepal mega earthquake in 2015 after a year of the event. Methods: A community based, cross sectional, descriptive study was carried out in Bhumlichaur area of Gorkha district, Nepal after around 14 months of the first major earthquake. We used self-reporting questionnaire 20, Posttraumatic stress disorder 8 and hospital anxiety and depression scale to screen for presence of symptoms of anxiety and depression or post-traumatic stress disorder in this population. The risk of having these disorders according to different socio-demographic variable was assessed by calculating odds ratio. All calculations were done using predictive and analytical software (PASW) version 16.0. Results: A total of 198 participants were included in the final data analysis. The mean age of study participants was 35.13 years (SD=18.04). Borderline anxiety symptoms were found in 104 (52.5%) while significant anxiety symptoms were found in 40 (20%) of respondents. Borderline depressive symptoms were seen in 40 (20%) while significant depressive symptoms were seen in 16 (8%) of subjects. Around 27% (n= 53) of respondents were classified as having post-traumatic stress disorder. Conclusions: The prevalence of anxiety and depressive symptoms and post-traumatic stress disorder seems to be high even after one year in people exposed to earthquake.